Are Homemade and Commercial Infant Foods Different? A Nutritional Profile and Food Variety Analysis in Spain - Bernal, Maria Jose (Nutrients, 2021)
Complementary feeding (CF) is an important determinant of early and later life nutrition with great implications for the health status and the development of an adequate growth. Parents can choose between homemade foods (HMFs) and/or commercial infant foods (CIFs). There is no consistent evidence as to whether HMFs provide a better nutritional profile and variety over CIFs. The aim of this study was to compare the nutritional profiles and food variety of HMFs versus CIFs in the Spanish market targeted for infants (6–11 months) and young children (12–18 months). Thirty mothers with their children aged 6 to 18 months were included in this cross-sectional study, following a 3-day weighed food diary of which HMFs were collected and chemically analyzed. HMFs meals for infant provided significantly lower energy, higher protein and higher fiber, for young children provided significantly higher protein and fiber than CIFs meals. HMFs fruit purees for infant shown significantly higher fiber and for young children provided higher energy than CIFs. HMFs meals contained a significantly greater number of different vegetables than CIFs meals (3.7 vs. 3.3), with carrot as the most frequently used in both. However, in CIFs fruit purees shown higher different fruits than HMFs, in both the banana was the fruit most frequently used. There was a predominance of meat and lack of oily fish and legumes in both HMFs and CIFs meals. HMFs and CIFs were equally characterized by a soft texture and yellow-orange colours. Importantly, our findings emphasize the need for clear guidelines for the preparation of HMFs as well as the promotion of food variety (taste and textures) in both HMFs and CIFs to suit infants’ and young children’s nutritional and developmental needs.